Photocatalytic Activity of ZnO/Hydroxyapatite Nanocomposite for Remazol Red RB Removal in Aqueous Solution Under UV and Visible Light Irradiation - I Dewa Ketut Sastrawidana; Luh Putu Ananda Saraswati; I Nyoman Sukarta; Ni Made Wiratini; I Ketut Sudiana; I Wayan Suja (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Textile industry wastewater contains synthetic dyes that are resistant to natural degradation, toxic, and capable of polluting aquatic environments. One commonly used dye is Remazol Red RB (RRRB), which is stable and difficult to remove through conventional treatment methods. Therefore, an effective approach is needed to break down this pollutant. This study aimed to develop and characterize a zinc oxide/hydroxyapatite (ZnO/HA) nanocomposite as a photocatalyst for degrading RRRB dye and to evaluate its photocatalytic performance under UV and visible light irradiation. The ZnO/HA nanocomposite was prepared by mixing ZnO and HA at a 1:1 ratio, followed by the addition of a small amount of water. The mixture was milled for 24 hours to obtain nanoscale particles. The resulting material was calcined at 700 °C and characterized using FTIR, XRD, and SEM-EDX to determine its physicochemical properties. Photocatalytic activity tests of the ZnO/HA nanocomposite toward RRRB dye solution were conducted in a batch system under 50-watt UV and visible light irradiation. The operational variables examined included catalyst dosage, initial pH, and dye concentration. FTIR analysis showed characteristic absorption bands of ZnO and HA, indicating successful formation of the nanocomposite. XRD results revealed a crystal size of 19.67 nm, while SEM-EDX confirmed the presence of Zn, Ca, P, and O elements, consistent with the nanocomposite composition. The degradation efficiency of 300 mL of 50 mg/L of RRRB solution at pH of 5 with 2.0 g of ZnO/HA nanocomposite under 50 watts of UV and visible light in succession was 90.43% and 80.93% for 120 minutes of irradiation.  Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).